The New Area-Wide Model II: An extended version of the ECB's micro-founded model for forecasting and policy analysis with a financial sector - Günter Coenen; Peter Karadi; Sebastian Schmidt; Anders Warne (European Central Bank (ECB), 2018)
This paper provides a detailed description of an extended version of the ECB's New Area-Wide Model (NAWM) of the euro area (cf. Christoffel, Coenen, and Warne 2008). The extended model - called NAWM II - incorporates a rich financial sector with the threefold aim of (i) accounting for a genuine role of financial frictions in the propagation of economic shocks and policies and for the presence of shocks originating in the financial sector itself, (ii) capturing the prominent role of bank lending rates and the gradual interest-rate pass-through in the transmission of monetary policy in the euro area, and (iii) providing a structural framework useable for assessing the macroeconomic impact of the ECB's large-scale asset purchases conducted in recent years. In addition, NAWM II includes a number of other extensions of the original model reflecting its practical uses in the policy process over the past ten years.
Keywords: C11; C52; E30; E37; E58; 330; DSGE modelling; Bayesian inference; financial frictions; forecasting; policy analysis; euro area